The Grasping Imagination : The American Writings of Henry James - Buitenhuis, Peter (Book collections on Project MUSE., 1973)
There has been almost no study of the American writings of Henry James, that is, the fiction, essays, and travel literature with an American setting. The great bulk of Jamesian criticism deals with the international novels, particularly his late works. This study places James's career in a new perspective by discussing its American aspect. It gives the critic an opportunity to come to grips with the evolution of James's technique from his second short story to his penultimate, unfinished novel, The Ivory Tower.